Mechanical, electrical and thermal properties of multi-walled carbon nanotubes/epoxy composites : effect of post-processing techniques and filler loading - Ervina, Junaidi; Mariattia, M.; Sinin, Hamdan (Springer Verlag, 2017)
In this study, MWCNT/epoxy composites were fabricated via combination of ultrasonication with two post-processing techniques namely, casting and hotpressing, respectively. The effect of these two post processing techniques and MWCNT loading ranging from 0 to 1.0 vol% on the mechanical, electrical and thermal properties of MWCNT/epoxy composites were investigated. The addition of MWCNT in epoxy reduced the tensile strength and tensile modulus of the MWCNT/epoxy composites compared to unfilled epoxy. However, the MWCNT/ epoxy composites prepared by hot-pressing technique improved the tensile strength and tensile modulus at 0.4 vol% MWCNT loading as confirmed by morphological analysis. The DMA properties of MWCNT/epoxy composites prepared by both post-processing techniques showed no significant change in storage modulus and Tg values. The increment of MWCNT loading slightly increased the electrical and thermal properties of MWCNT/epoxy composites via the hot-pressing technique. These findings indicate that different post-processing techniques and filler loading govern the properties of MWCNT/epoxy composites.